2001
DOI: 10.2337/diabetes.50.11.2431
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A Preferentially Excites Glucose-Sensitive Neurons in the Lateral Hypothalamus of the Rat In Vitro

Abstract: Falls in blood glucose induce hunger and initiate feeding. The lateral hypothalamic area (LHA) contains glucose-sensitive neurons (GSNs) and orexin neurons, both of which are stimulated by falling blood glucose and are implicated in hypoglycemia-induced feeding. We combined intracellular electrophysiological recording with fluorescein labeling of GSNs to determine their neuroanatomic and functional relationships with orexin neurons. Orexin A (1 mol/l) caused a 500% increase (P < 0.01) in spontaneous firing rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…The preceding results are in agreement with those obtained from in vitro studies that have reported that Hcrt produces neuronal depolarization (Horvath et al, 1999;Bayer et al, 2001;Eggermann et al, 2001;Eriksson et al, 2001;Liu et al, 2001Liu et al, , 2002Brown et al, 2002;Soffin et al, 2002) and changes in membrane conductance (Eriksson et al 2001;Burlet et al 2002). However, in neurons of the locus coeruleus, the application of Hcrt promotes depolarization accompanied by a decrease or no change in membrane conductance (Hagan et al, 1999;Ivanov and Aston-Jones, 2000).…”
Section: Time Constantssupporting
confidence: 82%
“…The preceding results are in agreement with those obtained from in vitro studies that have reported that Hcrt produces neuronal depolarization (Horvath et al, 1999;Bayer et al, 2001;Eggermann et al, 2001;Eriksson et al, 2001;Liu et al, 2001Liu et al, , 2002Brown et al, 2002;Soffin et al, 2002) and changes in membrane conductance (Eriksson et al 2001;Burlet et al 2002). However, in neurons of the locus coeruleus, the application of Hcrt promotes depolarization accompanied by a decrease or no change in membrane conductance (Hagan et al, 1999;Ivanov and Aston-Jones, 2000).…”
Section: Time Constantssupporting
confidence: 82%
“…A subpopulation of orexin neurons possess leptin receptors (Willie et al, 2001), and leptin administration is known to modulate the rewarding effect of lateral hypothalamic stimulation (Fulton et al, 2000). Furthermore, orexin neurons are sensitive to metabolic state, receiving input from glucose-sensitive neurons (Liu et al, 2001). One model of the role of the orexin modulation of VTA neurons could be as follows: lack of adequate metabolic substrate would lead to increased activity in orexin neurons, excitation of dopaminergic and GABAergic neurons in the VTA, leading to increased arousal, locomotor activity, and a search for food.…”
Section: Discussionmentioning
confidence: 99%
“…If the GABAergic input to PF LH neurons participates in appetite-related neural circuitry, then, based on previous literature, we expect certain profiles of glucose response characteristics of the synaptic transmission in PF LH (Liu et al, 2001;Song et al, 2001;Wang et al, 2004). In these experiments, the external concentration of glucose was lowered from 10 to 1 mM.…”
Section: Glucose and Nicotine Sensitivity Of Gabaergic Inputs To Pf Lmentioning
confidence: 99%